Enhancing Harmonics Mitigation of 5-Level Cascaded H-Bridge Inverter Through Fuzzy Proportional Voltage Balancing Control - Yong, Swee Xiang; Yap, Hoon; Mun, Hou Kit; Low, Foo Wah (International Journal of Integrated Engineering, 2026)
This work presents a novel approach to enhancing harmonics mitigation in 5-level cascaded H-Bridge inverters (5-lv CHB) through a Fuzzy Proportional Voltage Balancing Control technique. The proposed technique is applied to a Shunt Active Power Filter (SAPF) system to effectively reduce Total Harmonic Distortion (THD) in power systems. By dynamically balancing the voltages of the inverter’s DC-link capacitors, the proposed technique minimizes overshoot and ripple in the output waveform, ensuring a more stable and efficient operation. Simulation and experimental results demonstrate that the proposed technique significantly outperforms traditional voltage balancing technique, achieving improved harmonic suppression and reduced THD under varying load conditions. This approach provides a robust solution for enhancing power quality in modern power systems.